Evaluación de la eficiencia de tres productos orgánicos a base de microorganismos benéficos en la producción de plántulas de chocho (lupinus Mutabilis Sweet), Latacunga, Cotopaxi 2022-2023. - Viracocha Llano, Vanessa Carolina (2023)
The objective of this research was to determine the efficiency of three organic products based on beneficial microorganisms on chocho seedlings. It is necessary to verify the effectiveness in the phytosanitary control of the pest (Delia platura Meigen) of the crop. The first phase (pilonera) was carried out in the Salache Sector and the second phase (field) in the parish of Pastocalle, Canton Latacunga, province of Cotopaxi. The methodology of the study is constituted in a factorial arrangement of 3x3+1 with 10 treatments and 3 replications, resulting in 30 experimental units, a completely randomized block design (D.B.C.A). The organic products used were Solu biomix (Beauveria bassiana, Lecanicillium lecanii and Metarhizium anisopliae), Bio bass (Beauveria bassiana) and Bio metarhizium (Metarhizium anisopliae), in three different frequencies for each application. The results of the study do not show statistical significance in most of the variables because the organic products and frequencies of application were similar, in pylon there was statistical significance in days to the appearance of true leaves for Factor A (Bio bass) with 15.56 and root length of the seedling (Bio metarhizium) with 9.24cm ; In the field for the variable Incidence of Delia platura Meigen there was no statistical significance since the behavior was similar, in the T10 treatment (Control) with 3.7% represents the lowest presence of the pest attack on the seedling in the field, however the methodology used is favorable to avoid 100% of seed loss at the emergence stage by this pest.